2017
DOI: 10.1373/clinchem.2017.277624
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Steroid Serum Panel Based on LC-MS/MS: Use in Detection of Adrenocortical Carcinoma

Abstract: Serum steroid paneling by LC-MS/MS is useful for diagnosing ACC by combining the measurement of steroid hormones and their precursors in a single analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 36 publications
3
59
0
6
Order By: Relevance
“…This so-called heterogeneity of steroidogenesis observed is a reflection of immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[15][16][17]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19]. Consistent with our recommendation, [17,18] were recommended.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This so-called heterogeneity of steroidogenesis observed is a reflection of immature and dedifferentiated cell features, which are the hallmark of ACC [11,13,[15][16][17]. To our knowledge, no serum or urinary steroid metabolites associated with prognostic factors in ACC have been demonstrated to date, but several papers have reported these were useful for the diagnosis of ACC [11][12][13][14][15][16][17][18][19]. Consistent with our recommendation, [17,18] were recommended.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, steroid profiling has emerged as a powerful novel diagnostic tool for ACC [11][12][13][14]. Previous reports demonstrated that examination of serum steroid metabolites using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12,13] or urine steroid metabolites using gas chromatography mass spectrometry (GC-MS) [15][16][17][18][19] are useful for distinguishing ACC from adrenocortical adenoma. Furthermore, the ENSAT recommends a biochemical workup for suspected ACC that includes serum cortisol, aldosterone, 17-hydroxyprogesterone, dehydroepiandrosterone sulfate (DHEAS), androstenedione, testosterone, and 17-beta-estradiol (http://www.ensat.org/page-1317312).…”
Section: Introductionmentioning
confidence: 99%
“…Third, we included in our series also ENSAT stage IV tumors, which are frequently associated with clinically more severe steroid phenotypes due to their large tumor mass. This fact, however, also applies to the two series referred to above (14,18) and that by Kerkhofs et al (15). Fourth, we deliberately excluded aldosterone-producing adenomas from our series.…”
Section: Discussionmentioning
confidence: 66%
“…The recent study by Taylor et al (18) described the development of an LC-MS/MS method for quantitation of 13 steroid hormones in serum and applied this method to different adrenal tumors. With the exception of 17-OH-pregnenolone, all analytes accessible in the method by Taylor et al were also quantified in the present paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation